Sámi Literature and Handicraft as Means of Communication - Svensson, Tom G. (Culture, 1984)
In this article various forms of expressive culture are treated. Different literary expressions as well as handicraft and art in modern form illustrate the general argument stressing the communicative aspect of ethnically defined art forms. Ethnic arts among the Sámi definitely add a significant dimension to their development of efficient means of ethno-political articulation. To achieve this aim it is necssary that the art producers unite the styles of cultural expressions from the two cultures concerned, that of the majority society and that of the ethnic minority. In this context the distinction between verbal and non-verbal communication is also discussed.